2014
DOI: 10.3233/jad-130461
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensities are associated with Amyloid Burden in APOE4 Non-Carriers

Abstract: Previous preclinical studies have suggested a close relationship between cerebrovascular disease (CVD) and Alzheimer’s disease. However, a direct correlation between CVD and amyloid burden has not yet been shown in humans. If there is a relationship between CVD and amyloid burden, it is possible that the apolipoprotein E4 (APOE4) genotype may have an effect on this relationship because APOE4 is a risk factor for the development of AD. We therefore evaluated the effects of APOE4 on the relationship between whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
(60 reference statements)
4
31
0
4
Order By: Relevance
“…However, the positive association between WMC and amyloid burden seemed to be predominant in the posterior brain regions, which are not the typical topography of AD but CAA. 34 Another study also reported that the volume of WMC was independently related to amyloid retention in patients with CAA but not in patients with AD. 35 On the basis of these findings, it can be speculated that WMC may be more closely linked to vascular amyloid deposition associated with CAA rather than parenchymal amyloid deposition characteristic of AD.…”
Section: Wmc and Amyloid Plaquesmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the positive association between WMC and amyloid burden seemed to be predominant in the posterior brain regions, which are not the typical topography of AD but CAA. 34 Another study also reported that the volume of WMC was independently related to amyloid retention in patients with CAA but not in patients with AD. 35 On the basis of these findings, it can be speculated that WMC may be more closely linked to vascular amyloid deposition associated with CAA rather than parenchymal amyloid deposition characteristic of AD.…”
Section: Wmc and Amyloid Plaquesmentioning
confidence: 97%
“…[27][28][29]31,32 However, there were also studies showing positive relationships between WMC and amyloid. 33,34 For instance, in sporadic AD patients, WMC at baseline was significantly related to the progression of amyloid deposition in 28 months, 33 suggesting that WMC might accelerate the aggregation of amyloid protein produced in situ. However, the positive association between WMC and amyloid burden seemed to be predominant in the posterior brain regions, which are not the typical topography of AD but CAA.…”
Section: Wmc and Amyloid Plaquesmentioning
confidence: 99%
See 3 more Smart Citations